2020
DOI: 10.1093/treephys/tpaa156
|View full text |Cite
|
Sign up to set email alerts
|

MYB_SH[AL]QKY[RF] transcription factors MdLUX and MdPCL-like promote anthocyanin accumulation through DNA hypomethylation and MdF3H activation in apple

Abstract: Heritable DNA methylation is a highly conserved epigenetic mark that is important for many biological processes. In a previous transcriptomic study on the fruit skin pigmentation of apple (Malus domestica Borkh.) cv. ‘Red Delicious’ (G0) and its four continuous-generation bud sport mutants including ‘Starking Red’ (G1), ‘Starkrimson’ (G2), ‘Campbell Redchief’ (G3) and ‘Vallee spur’ (G4), we identified MYB transcription factors (TFs) MdLUX and MdPCL-like involved in regulating anthocyanin synthesis. However, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…DhK is an essential precursor for the synthesis of anthocyanin. hence, the F3H gene plays an important role in the color development of plants [55]. The relevant gene of F3H was cloned from the snapdragon for the first time [56].…”
Section: Flavanone 3-hydroxylasementioning
confidence: 99%
“…DhK is an essential precursor for the synthesis of anthocyanin. hence, the F3H gene plays an important role in the color development of plants [55]. The relevant gene of F3H was cloned from the snapdragon for the first time [56].…”
Section: Flavanone 3-hydroxylasementioning
confidence: 99%
“…Regarding the promoter methylation of genes encoding MYB transcription factors, we observed a negative correlation between promoter methylation and gene expression levels in MdMYBPA1 and MdMYB1R1-like . In addition, the use of ‘Red Delicious’ and its derivative four-generation mutants revealed that the CG methylation level of the novel MYB transcription factors MdPCL-like and MdLUX was negatively associated with their expression levels and anthocyanin content [ 53 ]. Overall, our findings support the notion that DNA methylation plays a vital role in manipulating gene expression and anthocyanin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with a stable expression system, transient transformation provides an efficient, convenient and faster tool to analyze gene function ( Wroblewski et al, 2005 ; Liao et al, 2019 ). To date, transient expression of MYBs has been well characterized in anthocyanidin biosynthesis of various plants, including rose ( Rosa hybrida ), radish ( Raphanus sativus ), freesia ( Freesia hybrida ), gerbera ( Gerbera hybrida ), apple ( Malus domestica ), tobacco ( Nicotiana tabacum ) and others ( Shen et al, 2019 ; Fan et al, 2020 ; Li T. et al, 2020 ; Li Y. et al, 2020 , Li et al, 2021 ; Zhong et al, 2020 ). In our studies, transient expression assays were undertaken in a dataset (105 studies) to test the function of MYB TFs.…”
Section: Discussionmentioning
confidence: 99%